Boosting Nepalese Global Trade Performance through Trust and Reputation in Correspondent Banking - Adhikari, Hem Kumari; Kaur, Kamaljeet (Journal of Advanced Academic Research, 2026)
Nepal is an import-based country where International trade and foreign payments remain criticaleconomic challenge. In the context of increasing global fraud and de-risking practices,trustworthiness has become a key concern for banking industries. This study examines how thetrust and reputation of correspondent banks shape the international trade-finance performance ofNepalese commercial banks. Using Deductive approach and cross sectional non experimentalresearch design, 300 professionals from Nepalese all commercial banks with distinct departmentslike as: Remittance/ SWIFT, Compliance /AML, Trade Finance and Top Management. Astructured questionnaire under three subheadings i.e. reliability, compliance creditability andstability of relationship which are the dimensions of Trust and Reputation of a correspondentbanking were used to gain the aptitudes of professionals. Descriptive Analysis results show theconsistency of trust and reputations sub themes i.e. realibility, compliance credibility andstability of relationship. Chi-square tests' results establish the significant association betweenoverall trust/reputation and trade finance facilitation performance measured as χ² = 2115.276, p